Noise Removal and QRS Detection of ECG Signal - Mou, Jannatul Robaiat; Islam, Sheikh Md. Rabiul; Huang, Xu; Ou, Keng Liang (British Journal of Healthcare and Medical Research, 2016)
In electrocardiogram (ECG), noise removal and QRS complex play the vital role for detecting various heart diseases. So, noise free and accurate QRS detection becomes very important in ECG signal. In this paper we are going to describe a new algorithms which are able to make it noise free and detect QRS complex in ECG signal. Generally, a noise free algorithm removes the noisy signal and we have used Remez exchange algorithm for 1st algorithm, designed an arbitrary magnitude with FIR filter for 2nd algorithm and FIR filter with window method for 3rd proposed algorithms. The noise free ECG signal of QRS complex can be detected by proposed detection algorithms. The performance parameters are SNR, PRD, MSE and Correlation and accuracy, sensitivity, specificity, precision are used to justify the proposed noise free algorithm and QRS detection. The real data examples and experimental results approve new algorithms which are more effective in ECG applications.